Linc-smad7 promotes myoblast differentiation and muscle regeneration via sponging miR-125b. Issue 6 (3rd June 2018) - Song, Chengchuang; Wang, Jian; Ma, Yilei; Yang, Zhaoxin; Dong, Dong; Li, Hui; Yang, Jiameng; Huang, Yongzhen; Plath, Martin; Ma, Yun; Chen, Hong
ABSTRACT: Long noncoding RNAs (lncRNAs) are involved in the regulation of skeletal muscle development. In the present study, differentially expressed lncRNAs were identified from RNA-seq data derived from myoblasts and myotubes. We conducted studies to elucidate the function and molecular mechanism of action of Linc-smad7 during skeletal muscle development. Our findings show that Linc-smad7 is upregulated during the early phase of myoblasts differentiation. In in vitro studies, we showed that overexpression of Linc-smad7 promoted the arrest of myoblasts in G1 phase, inhibited DNA replication, and induced myoblast differentiation. Our in vivo studies suggest that Linc-smad7 stimulates skeletal muscle regeneration in cardiotoxin-induced muscle injury. Mechanistically, Linc-smad7 overexpression increased smad7 and IGF2 protein levels. On the contrary, overexpression of miR-125b reduced smad7 and IGF2 protein levels. Results of RNA immunoprecipitation analysis and biotin-labeled miR-125b capture suggest that Linc-smad7 could act as a competing endogenous RNA (ceRNA) for miRNA-125b. Taken together, our findings suggest that the novel noncoding regulator Linc-smad7 regulates skeletal muscle development.